How Do Productive Zakat Promote MSMEs’ Resilience in Post-Pandemic Era? - Muhammad Nur Alam Muhajir; mujahidin (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The development of Micro, Small, and Medium Enterprises (MSMEs) has faced significant setbacks, particularly due to the COVID-19 pandemic. This study investigates the role of productive zakat in enhancing the resilience of MSMEs through a qualitative descriptive approach. Data were collected via interviews with 24 MSME actors and 3 productive zakat managers. The findings indicate that productive zakat contributes meaningfully to MSME resilience. Furthermore, the study highlights the relevance of human capital theory in business development, emphasizing the importance of skill enhancement and evaluation among MSME actors. The implications of this research support the ongoing resilience of MSMEs in the post-pandemic context and provide valuable insights for policymakers regarding productive zakat.